ANALISIS PENAMBATAN SENYAWA CHARANTIN DARI BUAH PARE (Momordica charantia) PADA GLUCOSE TRANSPORTER 3 (GLUT3) - Ilmia, Nisrien (Politeknik Tiara Bunda, 2025)
Glucose transporters have an important role in the body to transport blood sugar to other organs. In patients with diabetes mellitus, the signaling of GLUT, especially class 1, is reduced because it is affected by impaired insulin secretion. Bitter gourd is thought to have an anti-diabetic effect by lowering blood pressure, with the main component in it being charantin. Purpose: This study aims to determine the activity of charantin as a blood sugar lowering agent by inducing GLUT3 through a compound anchoring test. Methods: The type of research in this study was a computer-based experimental study using an in silico test or molecular docking by comparing the charantin test ligand and the native ligand as a comparison in the form of Octyl Glucose Neopentyl Glycol. Conclusion: The results of the compound anchoring test show that the binding energy (ΔG) affinity of charantin for GLUT3 is -7.5 Kcal/mol, while for Octyl Glucose Neopentyl Glycol it is -6.15 Kcal/mol, and charantin has activity like Octyl Glucose Neopentyl Glycol with amino acid residues that bind to the active site of the GLUT3 protein, namely AGR228. This indicates that the compounds present in bitter gourd can be predicted to be used as therapy for diabetes mellitus patients.